Galicia on literаry map of different national literatures (Late XVII – early XX century) (Literatures of the World: Poetics, Mentality and Spirituality, 2018)
The historical aspects of forming the literary map of Galicia in the works of writers of dominant nationalities living on this territory including Ukrainians, Poles, Austrians and Jews have been characterised. It has been determined that cultural landscape is an important component of the literary presentation of the Galician borderlands. This concept is closely linked with the idea of a map by means of which the authors build their own geographic space in their works. Literary maps become a reflection of the cultural landscape and restructure a certain territory at the same time. Each writer draws his own map of Galicia which defines his cultural landscape, including his own geography, history, culture and language.
Keywords: Galicia; identity; Galician literary borderlands; literary map; landscape; space; topos